2005
DOI: 10.1111/j.1439-0264.2004.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereological Study of the External Urethral Sphincter in the Female Urethra of the Lamb: A New Model for Studies on Urinary Continence

Abstract: Some of the morphometrical features and functional properties of the lamb external urethral sphincter (EUS) were determined by means of ATPase histochemistry. In this study, eight female urethras of 2- to 3-month-old lambs were used. The samples were studied by using an unbiased stereological design and were statistically evaluated with a Kolmogorov-Smirnov test. Additionally, the mechanical activity of the different fibre types was analysed by measuring the isometric changes in tension induced by electrical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…B). This observation is consistent with a previously published description of EUS in lambs (Rodriguez‐Veiga et al, ). Our data show that a short vestibular part of EUS is present in goats as it ends in the vestibular wall few millimeters caudally from the external urethral orifice.…”
Section: Discussionsupporting
confidence: 93%
“…B). This observation is consistent with a previously published description of EUS in lambs (Rodriguez‐Veiga et al, ). Our data show that a short vestibular part of EUS is present in goats as it ends in the vestibular wall few millimeters caudally from the external urethral orifice.…”
Section: Discussionsupporting
confidence: 93%
“…There is a great variability in given names for the urethral striated musculature possibly due to particular morphological differences between mammal species . For example, urethral sphincter in female rats is composed of striated fibers surrounding urethra that are closely associated with this viscera .…”
Section: Discussionmentioning
confidence: 99%
“…There is a great variability in given names for the urethral striated musculature possibly due to particular morphological differences between mammal species. 10,[19][20][21] For example, urethral sphincter in female rats is composed of striated fibers surrounding urethra that are closely associated with this viscera. 10 The SUS in women has three portions, the compressor urethrae and urethrovaginal sphincter covering the urethra and vagina; 2 and the urethral rhabdosphincter surrounding the urethra.…”
Section: Discussionmentioning
confidence: 99%
“…An in‐depth knowledge of the fiber‐type composition of the EUS is essential to evaluate its functional and metabolic properties. Both early and more recent enzyme‐based and immunohistochemical analyses have demonstrated the composition of the fiber types in the EUS of different species and in both sexes of animals, including human beings (Gosling et al, ; Schrøder and Reske‐Nielsen, ; Tokunaka et al, ; Sautet et al, ; Tokunaka et al, ; Praud et al, ; Rodrígues‐Veiga et al, ; Biérinx and Sebille, ; Buffini et al, ; Chen et al, ). Immunostaining for fast and slow myosin heavy chain (MHC) isoforms has shown that the female rat EUS contains mainly Type 2 (fast) and Type 1 (slow) fibers (Praud et al, ).…”
mentioning
confidence: 99%